2021
DOI: 10.3389/fevo.2021.654560
|View full text |Cite
|
Sign up to set email alerts
|

Linking Ecosystem Services to Social Well-Being: An Approach to Assess Land Degradation

Abstract: Land degradation usually leads to the loss of ecosystem services, which may threaten social well-being. There is no approach to identify and manage all ecosystem services based on their importance in degradation processes and social systems. This study aimed to link ecosystem services to social well-being in order to assess rangeland degradation. Eleven ecosystem services (forage production, water yield, edible plants, fuel, medicinal plants, pollination, gas regulation, soil resistivity to erosion, soil ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Therefore, reducing functional diversity or changing its composition could alter the supply of cultural services and affect good social relationships and freedom of choice by Indigenous Peoples. Sometimes a minor change in ecosystem services can trigger substantial changes when the loss exceeds certain thresholds (Sharafatmandrad & Khosravi Mashizi, 2021). Thereby, the protection of sites, species, or ecosystems of special significance improves the morale of large populations and the ability of self-determination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reducing functional diversity or changing its composition could alter the supply of cultural services and affect good social relationships and freedom of choice by Indigenous Peoples. Sometimes a minor change in ecosystem services can trigger substantial changes when the loss exceeds certain thresholds (Sharafatmandrad & Khosravi Mashizi, 2021). Thereby, the protection of sites, species, or ecosystems of special significance improves the morale of large populations and the ability of self-determination.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that ecosystem services offer many benefits to human wellbeing [69,70]. In the "grain-grain" transformation, economic production services have directly or indirectly impacted on four dimensions of well-being.…”
Section: The Relationship Between Ecosystem Services and Human Well-b...mentioning
confidence: 99%
“…Consequently, it remains unclear of what constitutes land degradation (von Maltitz et al, 2019), which explains why there is conspicuous absence of sound frameworks to guide policy formulation and the implementation of actionable adaptation strategies. In attempting to bridge this gap, recent studies suggest that LULC change be viewed from the perspective of the ecosystem goods and services that communities accrue from communal lands (Palmer and Bennett, 2013;Willemen et al, 2018;Sharafatmandrad and Mashizi, 2021;Kuule et al, 2022). This reasoning is informed by a scientifically premised realization of the fact that spatial and temporal variations in the distributions of the critical LULC types have far-reaching adverse impacts on sustainable access to ecosystem services and livelihoods of local communities.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, ecosystem service values provided by grassland, forest, and shrubland, declined due to the expansion of cropland, which was associated with human population growth and increasing demands for food (Belay et al, 2022). In Iran, change in plant compositions resulted in the decline of forage and medicinal plants (Sharafatmandrad and Mashizi, 2021). In Uganda, grasslands were overtaken by cropland and built-up area, while tree loss was reportedly associated with land privatization, land clearing, and fuelwood extraction (Kuule et al, 2022).…”
Section: Introductionmentioning
confidence: 99%